Melanocortin 4 receptor–mediated effects of amylin on thermogenesis and regulation of food intake. Issue 5 (28th March 2019) - Li, Xiaojing; Fan, Kuikui; Li, Qiang; Pan, Deng; Hai, Rihan; Du, Chenguang
Abstract: Aims: Amylin, a pancreatic hormone cosecreted with insulin, exerts important anorexic and weight‐loss effects. Melanocortin 4 receptor (MC4R) signalling plays a critical role in energy homeostasis; however, its role on amylin‐dependent regulation of food intake and adaptive thermogenesis of interscapular brown adipose tissue (IBAT) are unclear. In this study, we examined the effects of amylin on food intake and thermogenesis on IBAT via the MC4R pathway in mice. Materials and methods: Acute food consumption and thermogenesis in IBAT were measured in male wild‐type (WT) and MC4R‐deficient mice following intraperitoneal injection of amylin and SHU9119, an MC3R/4R antagonist, to determine the role of the central melanocortin system on the hypothalamus and IBAT. Results: Amylin (50 μg/kg) suppressed feeding and stimulated thermogenesis on IBAT via activation of the MC4R system in mice. Pharmacological blockade of MC4R using SHU9119 (50 μg/kg) attenuated amylin‐induced inhibition of feeding and stimulation of thermogenesis in IBAT. No changes were observed when SHU9119 was injected alone. Moreover, amylin significantly increased MC4R expression and c‐Fos neuronal signals in the arcuate nucleus and significantly increased acetyl‐CoA carboxylase (ACC) phosphorylation in the hypothalamus and IBAT and uncoupling protein‐1 (UCP1) expression in the IBAT of WT mice via the MC4R pathway. Conclusion: The melanocortin system was involved in amylin‐induced suppression of food intake and activation of thermogenesis in both the hypothalamus and IBAT via modulation of ACC phosphorylation and UCP1 expression.